Anisotropic and Self‐Healing Copolymer with Multiresponsive Capability via Recyclable Alloy‐Mediated RDRP. Issue 12 (13th April 2021) - Mohammad, Sk Arif; Dolui, Subrata; Kumar, Devendra; Alam, Md. Mehboob; Banerjee, Sanjib
Abstract: A novel triple stimuli sensitive block copolymer is prepared by magnetically separable and reusable (up to multiple cycles) Ni–Co alloy nanoparticles mediated reversible deactivation radical polymerization (RDRP) at 25 °C, that responds to changes in temperature, pH, and light. Design of this block copolymer constitutes a temperature‐sensitive N ‐isopropylacrylamide (NIPAM), an acid‐sensitive lysine methacrylamide (LysMAM), and a light responsive umbelliferone (UMB) end group. The stimuli response, in response to one stimulus as well as combinations of stimuli, has been evaluated. Responsiveness to light allows the construction of self‐healing materials. Density functional theory calculations rationalize the underlying mechanism of the polymerization. Abstract : A novel triple stimuli sensitive block copolymer that responds to changes in temperature, pH, and light is prepared by magnetically separable and reusable (up to multiple cycles) Ni–Co alloy nanoparticles mediated reversible deactivation radical polymerization (RDRP) at 25 °C.